PENERAPAN GREEN HUMAN RESOURCES MANAGEMENT PADA HOTEL NEW SUNARI LOVINA BEACH RESORT - Komang Krishna Darmawan; Luh Linna Sagitarini; I Gusti Agung Mas Krisna Komala Sari (Jurnal Manajemen Perhotelan dan Pariwisata, 2022)
This research is a qualitative descriptive study that aims to analyze the application of Green Human Resource Management to management commitment, especially in the human resources department, which will lead to the formation of green employee performance in carrying out their work in operations. This research was conducted at New Sunari Lovina Beach Resort for three months with data collection methods, namely interviews, observation, documentation, and literature study. The sample used in the interview process is hotel management, totaling eight people, namely department heads in all departments. The results of this study indicate that the application of Green Human Resource Management at New Sunari Lovina Beach Resort has been implemented but is not optimal. The not yet optimal implementation of Green Human Resources Management at New Sunari Lovina Beach Resort is caused by several factors, including the unstructured Standard Operating Procedure (SOP), management commitment, and a limited budget.